IMPACT OF HEAVY METAL CONTAMINATION ON PHYTOCHEMICAL PROFILES IN MARINE CRUSTACEANS: A COMPARATIVE STUDY OF Farfantepenaeus notialis AND Macrobrachium vollenhovenii - Ayanniyi, Oluwadamilola A.; Ibitoye, Oluwatosin S.; Ayeni, Olabisi H.; Ademola, Oluwafunke C.; Aremu, Emmanuel Ayanniyi; Wealth, Abiola S.; Murtala, Muniru O.; Chiawa, Okwudili C.; Muritala, D. S.; Adenika, O. A. (FUDMA JOURNAL OF SCIENCES, 2024)
Heavy metal contamination poses significant risks to marine ecosystems and human health. This study investigates the impact of heavy metal contamination on the phytochemical profiles of two marine crustacean species, Farfantepenaeus notialis and Macrobrachium vollenhovenii. Samples of these crustaceans were collected from Bodija Market, Ibadan, Nigeria, and analyzed for heavy metal content (Cu, Cd, Pb, Hg, As) and phytochemical constituents including alkaloids, flavonoids, saponins, tannins, anthraquinones, terpenoids, cardiac glycosides, steroids, and phenols. The heavy metal analysis revealed that Farfantepenaeus notialis had concentrations of Cu at 0.592 ± 0.03 mg/g and Pb at 0.080 ± 0.06 mg/g, while Macrobrachium vollenhovenii had lower concentrations of Cu (0.331 ± 0.07 mg/g) and Pb (0.061 ± 0.02 mg/g). Phytochemical screening showed that Farfantepenaeus notialis had higher levels of alkaloids (1.65 ± 0.004% w/w), flavonoids (0.35 ± 0.17% w/w), and saponins (0.80 ± 0.002% w/w) compared to Macrobrachium vollenhovenii, which had lower concentrations of these compounds (alkaloids: 0.75 ± 0.002% w/w, flavonoids: 0.12 ± 0.10% w/w, saponins: 0.75 ± 0.001% w/w). Both species were positive for steroids and cardiac glycosides but lacked detectable levels of tannins and phenols. These results indicate that heavy metal contamination significantly influences the phytochemical composition of marine crustaceans. The higher heavy metal levels in Farfantepenaeus notialis correlated with higher phytochemical concentrations, whereas Macrobrachium vollenhovenii showed lower phytochemical levels, possibly due to its lower heavy metal accumulation. This comparative analysis underscores the need for ongoing monitoring of heavy metal pollution in marine environments and its effects on aquatic organisms’ biochemical profiles.